Psychological inflation: Definition and measurement - Pham, Thi Thanh Xuan; Nguyen, Thi Canh; Ho, Huu Tin (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
Conventional monetary policy tools became less effective, with nominal short-term interest rates approaching the zero-lower bound during COVID-19. Instead, central banks adopted a range of unconventional monetary policies. Thus, perceived inflation has become a key channel for monetary policy transmission. Despite how vital perceived inflation is, quantifying perceived inflation with accuracy remains questionable and challenging. As a result, we focus on developing a novel measurement of perceived inflation - the psychological inflation index. Our approach is based on psychological theories and considers loss aversion, which creates advancements to previous versions. The new index satisfies many expected criteria: (i) it broadly co-moves with the headline inflation index during everyday contexts; (ii) it captures abnormal price evolution better than headline inflation during crisis periods; (iii) it links tightly with monetary policy and economic dynamics. Psychological inflation, therefore, might be helpful in forecasting headline inflation, estimating real interest rates, predicting economic players’ behavior, and setting salaries and prices. Psychological inflation, combined with headline inflation, provides a clearer picture of the credibility of monetary policy.